The Discovery and Preliminary Geological and Faunal Descriptions of Three New Steinahóll Vent Sites, Reykjanes Ridge, Iceland - Taylor, James; Devey, Colin; Le Saout, Morgane; Petersen, Sven; Kwasnitschka, Tom; Frutos, Inmaculada; Linse, Katrin; Lörz, Anne-Nina; Pałgan, Dominik; Tandberg, Anne H.; Svavarsson, Jörundur; Thorhallsson, Daniel; et al. (Frontiers in Marine Science, 2021)
During RV MS Merian expedition MSM75, an international, multidisciplinary team explored the Reykjanes Ridge from June to August 2018. The first area of study, Steinahóll (150–350m depth), was chosen based on previous seismic data indicating hydrothermal activity. The sampling strategy included ship- and AUV-mounted multibeam surveys, Remotely Operated Vehicle (ROV), Epibenthic Sledge (EBS), and van Veen grab (vV) deployments. Upon returning to Steinahóll during the final days of MSM75, hydrothermal vent sites were discovered using the ROV Phoca (Kiel, GEOMAR). Here we describe and name three new, distinct hydrothermal vent site vulnerable marine ecosystems (VMEs); Hafgufa, Stökkull, Lyngbakr. The hydrothermal vent sites consisted of multiple anhydrite chimneys with large quantities of bacterial mats visible. The largest of the three sites (Hafgufa) was mapped, and reconstructed in 3D. In total 23310 individual biological specimens were sampled comprising 41 higher taxa. Unique fauna located in the hydrothermally venting areas included two putative new species of harpacticoid copepod (Tisbe sp. A and Amphiascus sp. A), as well as the sponge Lycopodina cupressiformis (Carter, 1874). Capitellidae Grube, 1862 and Dorvilleidae Chamberlin, 1919 families dominated hydrothermally influenced samples for polychaetes. Around the hydrothermally influenced sites we observed a notable lack of megafauna, with only a few species being present. Whilst we observed hydrothermal associations, the overall species composition is very similar to that seen at other shallow water vent sites in the north of Iceland, such as the Mohn Ridge vent fields, particularly with peracarid crustaceans. We therefore conclude the community overall reflects the usual “background” fauna of Iceland rather than consisting of “vent endemic” communities as is observed in deeper vent systems, with a few opportunistic species capable of utilizing this specialist environment.